Capital Account Liberalization, Capital Flow Patterns, and Policy Responses in the EU's New Member States - Arvai, Zsofia (IMF Working Papers; Working Paper ;, 2005)
This paper discusses the experience of the EU's eight new member countries (EU8) between 1995 and 2003 when the bulk of capital account liberalization took place, focusing on interest-rate-sensitive portfolio flows and financial flows. It takes stock of the lessons from capital flow patterns to draw policy conclusions. There were two distinct groups in terms of the speed of capital account liberalization: rapid liberalizers and cautious liberalizers. The speed of disinflation and the level of public debt were major determinants of the size of interest-rate-sensitive portfolio inflows. Monetary and exchange rate policies were the main instruments used to react to large interest-sensitive inflows, whereas fiscal tightening was seldom used as a direct reaction to inflows.